Handling of Domestic Tourists by Tour Guides at CV. Wali Wali Makassar - A Tri Hendra Gunawan; Margaretha Wadid Rante; Darmayasa Darmayasa (Politeknik Pariwisata Makassar, 2024)
The number of tourists in Indonesia has increased rapidly, and one of the key factors contributing to this is the demand for tour package trips. Domestic tourists are one of the market segments that generate revenue for travel agencies. With this high demand, travel agencies must ensure that domestic tourists are handled properly by tour guides. Therefore, this study aims to (1) understand the preparations for tourist trips by CV. Wali Wali Makassar and (2) identify the qualifications of the tour guides at CV. Wali Wali Makassar. This research uses a qualitative approach. The researcher collected data using direct interviews with key informants and through literature review. Data analysis was conducted by gathering, managing, analyzing, presenting data, and drawing conclusions descriptively from the primary data obtained through interviews and direct documentation from the operational staff at CV. Wali Wali Makassar's tour package office. Secondary data sources consisted of documents and written reports obtained from parties that supported the primary data related to the research topic. Conclusions were drawn based on reduced data from the informants. The results of this research indicate that (1) the preparation for tourist trips conducted by CV. Wali Wali Makassar is not yet optimal and faces several challenges. The main challenge that needs attention is the lack of safety equipment during emergencies, such as the absence of a first aid kit at CV. Wali Wali Makassar. (2) The qualifications of the tour guides used in the tour packages at CV. Wali Wali Makassar are not yet fully met, even though the company pays attention to various important factors to ensure proper tourist handling based on the established standard operating procedures. The lack of adequate tour guide qualifications has become an obstacle in executing tour packages. These factors need to be addressed to ensure optimal handling of tourists based on the standard operating procedures set by CV. Wali Wali Makassar.